2014
DOI: 10.5713/ajas.2014.14562
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Feed Energy Density and a Formulated Additive on Rumen and Rectal Temperature in Hanwoo Steers

Abstract: The present study investigated the optimum blending condition of protected fat, choline and yeast culture for lowering of rumen temperature. The Box Benken experimental design, a fractional factorial arrangement, and response surface methodology were employed. The optimum blending condition was determined using the rumen simulated in vitro fermentation. An additive formulated on the optimum condition contained 50% of protected fat, 25% of yeast culture, 5% of choline, 7% of organic zinc, 6.5% of cinnamon, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…High-fibre diets favour the production of acetate over propionate. Inefficient ATP production using acetate as a substrate is now thought, in part, to cause the high DIT measured in ruminants (Cho et al, 2014). As testament to the thermogenic effects of acetate, this substrate is preferentially oxidised when an animal is cold-challenged, leaving larger amounts of amino acids relative to glucose available for growth and reproduction than would be available at thermoneutrality (Baumgard & Rhoads, 2012).…”
Section: (1) Obligatory Thermogenesismentioning
confidence: 99%
“…High-fibre diets favour the production of acetate over propionate. Inefficient ATP production using acetate as a substrate is now thought, in part, to cause the high DIT measured in ruminants (Cho et al, 2014). As testament to the thermogenic effects of acetate, this substrate is preferentially oxidised when an animal is cold-challenged, leaving larger amounts of amino acids relative to glucose available for growth and reproduction than would be available at thermoneutrality (Baumgard & Rhoads, 2012).…”
Section: (1) Obligatory Thermogenesismentioning
confidence: 99%
“…Gaughan, Mader, Holt, Hahn and Young (2002) reported that animals in thermal stress reduced the DMI as a way to regulate their body temperature. Nevertheless, using yeast in the cattle diet reduces the ruminal and rectal temperature (Cho et al, 2014), and increases the DMI. Our results highlighted that crossbred animals supplemented with yeast showed a greater ADG than the control group.…”
Section: Discussmentioning
confidence: 99%
“…Certain food additives decreased the temperature of the rumen of steers by optimizing microbial fermentation to produce more propionate and less acetate. 15 Based on these data and the fact that diet influences human gut microbiota composition, 16 we suggest that foods can have warming or cooling properties depending on what changes they bring about in the microbiota. Could this help explain the traditional Chinese medicine concept of heating and cooling foods?…”
mentioning
confidence: 99%